2002
DOI: 10.1088/0953-2048/16/1/102
|View full text |Cite
|
Sign up to set email alerts
|

Transport critical current of solenoidal MgB2/Cu coils fabricated using a wind-reactionin situtechnique

Abstract: In this letter, we report the results of transport J c of solenoid coils upto 100 turns fabricated with Cu-sheathed MgB 2 wires using a wind-reaction in-situ technique. Despite the low density of single core and some reaction between Mg and Cu-sheath, our results demonstrate the decrease in transport J c with increasing length of MgB 2 wires is insignificant. Solenoid coils with diameter as small as 10 mm can be readily fabricated using a wind-reaction in-situ technique. The J c of coils is essentially the sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…For practical applications, long wires and demonstration devices should be fabricated. Generally speaking, compared to the short samples, there will be a Jc deterioration in the long wire [18]. But the Jc property of the long pnictide wire should be still acceptable for engineering uses.…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications, long wires and demonstration devices should be fabricated. Generally speaking, compared to the short samples, there will be a Jc deterioration in the long wire [18]. But the Jc property of the long pnictide wire should be still acceptable for engineering uses.…”
Section: Introductionmentioning
confidence: 99%
“…Soltanian, Dou, et al, [14] Musenich et al [21] reported on pancake coils wound from tape which carried 347 A at 4.2 K in the coil and generated 0.75 T.…”
Section: Introductionmentioning
confidence: 99%
“…Because the fabrication of MgB can occur by conventional metal-working processes, the barrier to experimentation is low. The problems of fabricating MgB conductors commercially are being addressed by Hyper Tech Research, Columbus, OH [101], Columbus Superconductors, Genova, Italy [102], Hitachi, Hitachi City, Japan, and NIMS in Japan [103], and many other laboratories worldwide, as a good recent survey makes clear [12]. Several groups have fabricated more than 100-m lengths of prototype wires.…”
Section: Magnesium Diboridementioning
confidence: 99%